PERENCANAAN STRUKTUR JEMBATAN SLAB ON PILE SUNGAI BRANTAS DENGAN MENGGUNAKAN METODE PRACETAK PADA PROYEK TOL SOLO – KERTOSONO STA. 176+050 – STA. 176+375 - Khrisnawan Arief Wicaksono; Kuni Saadati; Purwanto Purwanto; Sukamta Sukamta (Jurnal Karya Teknik Sipil, 2016)
Brantas Bridge is a bridge which includes the construction of Solo-Kertosono toll road development located on the river Brantas, District Patianrowo, Kertosono, Nganjuk, East Java. Total length of Brantas bridge about 890 m, for planning this bridge which relatively long, it needs several different methods, one of them is using slab on pile method on the part of approach bridge. The structure of slab on pile bridge of Brantas river planned to use precast prestressed concrete systems for plate elements. Loading standart on the structure refers to the SNI T-02-2005 (Standar Pembebanan Untuk Jembatan). Analysis and modelling structure was done by 3 steps are structure that has already function, when elevation of precast element, and when installation of precast element. The analysis of structure modeling done by support of SAP2000 software. The results of planning show that bridge structure of slab on pile in Brantas river was safe by analysis.